Pontos quânticos de carbono aplicado à determinação fluorimétrica de cobre(II) em óleos usando um sistema em fluxo-batelada com extração em fase única - Andrade, Stéfani Iury Evangelista de (2016)
In this work, a novel fluorescence method using flow-batch analysis for the determination of copper in edible oil, employing carbon quantum dots (CDs) was developed. The in-line single-phase extraction of iron consisted of the addition of a mixture of isopropyl alcohol/chloroform (70:30, v/v) to dissolve the oil samples. Moreover, an eco-friendly, simple, and low-cost hydrothermal method was developed for preparation of water-soluble fluorescent carbon quantum dots using pineapple juice as carbon precursors. The fluorescence properties of CDs were examined by fluorescent detection of Cu(II) in oil. Their photoluminescence can be significantly quenched by simply using the buffer solution PBS of pH 4.0. This mechanism was presumably explained by the interactions between the surface groups of CDs with metal ions studied. Concerning the flow-batch analysis a new mixing chamber was developed in polytetrafluoroethylene provided with quartz windows in order to allow the excitation and fluorescence detection online. For this, an LED UV was used as the excitation source and a portable spectrofluorometer as detector. The limits of detection and relative standard deviation were estimated as 2.9 μg L−1 and < 2.5 % (n=3). The analysis of interfering was successful for the major ions present in solution, revealing significant percentage interference (≤ 5 %).The precision of the method was evaluated by recovery test (96 to 106 %). The robustness of the method was evaluated by intra- and inter- day comparison of the results obtained and using the reference method with detection by atomic absorption graphite furnace at a 95% level of statistical confidence. Finally, the system showed quite satisfactory analytical frequency (60 h–1) and considerably reducing the consumption of chemicals. Thus, it is demonstrated appreciably the viability of new fluorescent method, thus allowing the development of new analytical strategies employing potentially useful carbon quantum dots and flow-batch analyzer.